Forecasting of Electrical Energy Consumption in Aceh 2028 Using the Adaptive Neuro Fuzzy Inference System - Muzammil Jusoh; Christin Erniati Panjaitan; Vito Sentosa (Journal of Electronics, Telecommunication, Electrical, and Physics Science, 2021)
Electricity consumption in Aceh is increasing from year to year. Factors causing increased electricity consumption in Aceh are Population Growth, and Economy. To meet the need for electricity consumption which is increasing from year to year, then it is forecast that the long-term consumption of electrical energy for 10 years is in 2028 in Aceh. To estimate the consumption of electrical energy requires a method that can approach the original results. The method is the Adaptive Neuro Fuzzy Inference System Method. The results obtained in estimating electricity consumption in 2028 in Aceh using this method amounted to 5578,02 GWh or with an increase of 2,07% every year until 2028.